Haploidentical Related Donor Hematopoietic Stem Cell Transplantation for Dedicator-of-Cytokinesis 8 Deficiency Using Post-Transplantation Cyclophosphamide - AYDINER, ELİF; BARIŞ, SAFA (ELSEVIER SCIENCE INC, 2017)
Dedicator-of-cytokinesis 8 (DOCK8) deficiency, a primary immunodeficiency disease, can be reversed by allogeneic hematopoietic stem cell transplantation (HSCT); however, there are few reports describing the use of alternative donor sources for HSCT in DOCK8 deficiency. We describe HSCT for patients with DOCK8 deficiency who lack a matched related or unrelated donor using bone marrow from haploidentical related donors and post-transplantation cyclophosphamide (PT/Cy) for graft-versus-host disease (GVHD) prophylaxis. Seven patients with DOCK8 deficiency (median age, 20 years; range, 7 to 25 years) received a haploidentical related donor HSCT. The conditioning regimen included 2 days of low-dose cyclophosphamide, 5 days of fludarabine, 3 days of busulfan, and 200 cGy total body irradiation. GVHD prophylaxis consisted of PT/Cy 50 mg/kg/day on days +3 and +4 and tacrolimus and mycophenolate mofetil starting at day +5. The median times to neutrophil and platelet engraftment were 15 and 19 days, respectively. All patients attained >90% donor engraftment by day +30. Four subjects developed acute GVHD (1 with maximum grade 3). No patient developed chronic GVHD. With a median follow-up time of 20.6 months (range, 9.5 to 31.7 months), 6 of 7 patients are alive and disease free. Haploidentical related donor HSCT with PT/Cy represents an effective therapeutic approach for patients with DOCK8 deficiency who lack a matched related or unrelated donor. Published by Elsevier Inc. on behalf of the American Society for Blood and Marrow Transplantation.
Keywords: Dedicator-of-cytokinesis-8 (DOCK8) deficiency; Haploidentical transplantation; Immune reconstitution; BONE-MARROW-TRANSPLANTATION; VERSUS-HOST-DISEASE; HYPER-IGE SYNDROME; CHRONIC GRANULOMATOUS-DISEASE; DOCK8 DEFICIENCY; HEMATOLOGIC MALIGNANCIES; COMBINED IMMUNODEFICIENCY; NONMALIGNANT DISORDERS; ALPHA-BETA; BLOOD